Human case of fasciolosis in Serbia treated with triclabendazole - Pavlovć, Milorad; Dakić, Zorica; Milošević, Branko; Korać, Miloš; Brmbolić, Branko; Džamić, Aleksandar (Vojnosanitetski pregled, 2014)
Introduction. The number of humans infected by Fasciola hepatica is increasing worldwide. Humans can become accidental hosts by ingesting drinking water or plants contaminated with metacercariae. Case report. We reported a case of a 68-year-old Serbian woman, in which the diagnosis of acute fasciolosis had been established after serious diagnostic concerns. Based on clinical picture (episodic right upper quadrant abdominal pain, febrility and generalized body pain) and biochemical analyses (high eosinophilia and high activity of alkaline phosphatase), she was appointed as suspected to the acute fasciolosis. Stool and duodenal aspirate exams were negative for Fasciola ova. In the absence of adequate serologic diagnostic for fasciolosis in Serbia, the diagnosis was confirmed using enzyme immunoassays and immunoblot at the Institute for Tropical Diseases in Hamburg, Germany. Soon after triclabendazole was administered, the symptoms disappeared and biochemical values returned to normal. Conclusion. The diagnosis of human fasciolosis may be problematic and delayed, especially in non endemic areas, because physicians rarely encounter this disease and a long list of other diseases must be considered in the differential diagnosis. The syndrome of eosinophilia, fever, and right upper quadrant abdominal pain suggest acute fasciolosis. Unclear source does not rule out fasciolosis.